2022
DOI: 10.1111/ced.15201
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning modules in undergraduate dermatology teaching

Abstract: Background. Dermatological diagnosis depends highly on visual skills, and implicit nonanalytical proficiency plays a key role. To correctly diagnose skin diseases, the clinician needs visual skills, and intuitive recognition plays a key role. Aim. To investigate the effectiveness of digital perceptual learning modules (PLMs) in undergraduate teaching, and how these affect medical students' learning about skin diseases. Methods. This was a study performed in Finland, which enrolled 39 students of an undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Digital technologies have developed into effective enhancements of medical education and have shown to produce rapid and enduring learning outcomes 12,42 . Methods of PL have been implemented in a variety of different specialities 43 but although dermatology is primarily a visual speciality, only a very limited amount of research exists 5,11,26 . Regarding the correct identification of skin lesions, studies have shown that most important factors are frequent repetitions and sufficient intervals between practice 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Digital technologies have developed into effective enhancements of medical education and have shown to produce rapid and enduring learning outcomes 12,42 . Methods of PL have been implemented in a variety of different specialities 43 but although dermatology is primarily a visual speciality, only a very limited amount of research exists 5,11,26 . Regarding the correct identification of skin lesions, studies have shown that most important factors are frequent repetitions and sufficient intervals between practice 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…A 10–15 s response time has been reported most effective in learning electrocardiogram interpretation 52,53 . We used a 10 s response time (images disappeared after 10s, but participants had 30s time to respond), which was shorter than in our previous study on PLMs 26 . Champagne et al 54 examined PLMs on postgraduate training of echocardiography with short‐time improvements, but no sustainment of learning effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations